Scaled seismotectonic models of megathrust seismic cycles through the lens of dynamical system theory - Fabio Corbi; Adriano Gualandi; Giacomo Mastella; Francesca Funiciello (Seismica)
We investigate the physics of laboratory earthquakes in scaled seismotectonic models of megathrust seismic cycles. We study models of different sizes, materials, deformation rates, and frictional configurations. We use nonlinear time-series analysis tools to characterize the dynamics of the models. Observations are described, on average, by a low-dimension (<5), similar to slow slip episodes in nature and friction experiments performed with quartz powder. Results seem insensitive to the along-strike frictional segmentation of the megathrust. Using displacement as an input variable, the instantaneous dimension and the instantaneous extremal index vary through the seismic cycles. We notice the highest values of the instantaneous dimension associated with slip phases. Under specific circumstances, clear drops of the instantaneous extremal index can serve as an early indicator of slip episodes. Prediction horizons in the order of slip duration mirror similar predictability as for slow slip episodes in nature. We conclude that seismotectonic models are effective tools to study frictional physics despite their different spatio-temporal scales.